Calorie Restriction Extends Lifespan in Yeast Independently of GCN5 (Bioresearch Communications, 2026)
Calorie restriction (CR) has been shown to increase longevity in various animals; however, the mechanisms by which it affects chromatin-modifying factors remain poorly understood. GCN5, a histone acetyltransferase, is a vital regulator of transcription that responds to metabolic and stress signals, linking nutrient signaling to chromatin remodeling, but the extent of its necessity in promoting longevity through caloric restriction (CR) has yet to be completely defined. We investigated chronological lifespan (CLS), growth dynamics, respiratory efficiency, oxidative stress tolerance, mitochondrial DNA (mtDNA) mutation rate, and mtDNA abundance in a yeast gcn5Δ mutant under both normal and glucose-restricted conditions in order to elucidate GCN5-independent effects of CR. Under CR, the mutant showed a significant increase in CLS along with a decreased growth rate and improved survival in the stationary phase. Despite the loss of GCN5, calorie restriction enhanced respiratory efficiency on non-fermentable substrates, improved survival under oxidative stress, increased mtDNA abundance, and reduced mtDNA mutations, suggesting improved mitochondrial integrity. Altogether, these results showed that CR can compensate for GCN5's absence by triggering alternative nutrient-sensing and mitochondrial maintenance systems. This information offers insights into chromatin-independent pathways that could be used to mitigate aging and mitochondrial dysfunction in higher organismsBioresearch Commu. 12(1): 1961-1971, 2026 (January)